Genomic and clinical characterization of linezolid resistance in Enterococcus species from cancer patients in China - Qun Wang; Xiaoyu Zhang; Weixing Wu; Zhenghua Xie; Yongping Lin; Li Zhang (BMC Infectious Diseases)
Abstract Background Immunocompromised cancer patients represent a susceptible population for enterococcal infections. While linezolid remains the primary therapeutic option for vancomycin-resistant Enterococcus (VRE) infections, the emergence of linezolid-resistant Enterococcus (LRE) worldwide has not only exacerbated public health risks but also posed significant challenges to clinical treatment. This study aimed to analyze the prevalence of LRE isolates among cancer patients in China and to investigate the mechanisms of linezolid resistance. Methods A total of 656 non-repetitive Enterococcus isolates were collected. The susceptibility of Enterococcus to linezolid was determined using the broth microdilution method, and the mechanisms of linezolid resistance were explored through whole-genome sequencing. Results Among 656 isolates, 22 (3.35%) of Enterococcus were found to be resistant to linezolid. The isolates were susceptible to tigecycline, teicoplanin and vancomycin, except for one isolate with vancomycin resistance. The optrA gene was the primary mechanism of acquired linezolid resistance. Eleven LRE isolates had mutations in rplD gene. None of Enterococcus isolates contained cfr or poxtA genes or had mutations in the 23 S rRNA or rplC genes. ST16 (8, 36.36%) was the most prevalent sequence type (ST) in LRE isolates. The optrA gene was predominantly located on the chromosome (15, 68.18%), and was often associated with the fexA gene. The RDK variant (8, 36.36%) was predominant variant of the OptrA protein. Conclusion The prevalence of LRE in this centre was low (3.35%). The presence of optrA gene was the primary mechanism of acquired linezolid resistance, with ST16 being the most prevalent sequence type. These findings highlight the need for both continued surveillance of LRE and further investigation into the role of OptrA variants in linezolid resistance.